Mathematical models for color parameter differentials in citrus reticulata juices influences of formulation and thermal process conditions - Vivas, Lara G., author; Gabriel, Alonzo Alulod (Quezon City: College of Home Economics, University of the Philippines Diliman,c2007)
ABSTRACT The influences of dilution, soluble solids, temperature and time of pasteurizations on the differential color parameters ∆L*, ∆a* and ∆b* of pasteurized dalandan juices were studied. An experimental design based on the Central Composite Rotatable Design (CCRD) of experiment was developed for the different Citrus Model Systems (CMSs). The color parameters (L*, a*, and b*) of each Citrus Model System (CMS) were measured using the HunderLab ColorFlex® Spectrophotometer. Color parameters of the control sample (freshly squeezed, no dilution, no soluble solid adjustment, and no pasteurization applied) was also taken. The differential color parameters ∆L* ( L*final - L*control), ∆a* ( a*final - a*control) and ∆b* ( b*final - b*control) were calculated and determined for each CMSs. Predictive models were developed and analyzed through Response Surface Methodology. Among the test variables studied, dilution provided the most significant influences for all the color parameters ∆L*, ∆a*, and ∆b*. The effect of soluble solids content was only significant in ∆L* and ∆b*. On the other hand, temperature only affected ∆L* and ∆a* while the influence of the time of pasteurization was only visible in ∆L*. Interactive influences of temperature and time was also observed in ∆L*, demonstrating that at any time value (in minutes) included in the range tested in the study, the ∆L* increased with decreasing temperature.
Keywords: Citrus juices -- Philippines -- Processing -- Mathematical model